The effect of variable environmental arsenic contamination on urinary concentrations of arsenic species. - Kalman, D A (1990)
Urinary arsenic species have been determined for approximately 3000 urine samples obtained from residents of a community surrounding an arsenic-emitting copper smelter. Levels of inorganic, monomethylated and dimethylated arsenic species ranged from less than 1 microgram/L (the instrumental detection limit) to 180 micrograms/L seen for dimethyl arsenic. Comparison of a subsample of this population that had the least environmental contamination with the subsample having highest environmental arsenic concentrations showed small but statistically significant differences in urinary arsenic levels for all species except dimethylated arsenic. However, for children under 7 years of age living in areas with increased environmental arsenic contamination, there was a larger and equally significant (p less than 0.001) increase in all urinary species. This effect was more pronounced in males (5-fold increase in median sum of species concentration over control group) than in females (2-fold increase in median sum of species concentration over control group) and was observed as a weaker effect in the next higher age group (7-13 years of age). Reported consumption of seafood also was significantly related to increased urinary dimethyl arsenic, but changes in distribution among the urinary arsenic species detected was not a sensitive indicator of recent seafood consumption.